IMPLEMENTASI MANAJEMEN KEAMANAN INFORMASI BERBASIS ISO 27001 PADA SISTEM INFORMASI AKADEMIK - Intan Mafiana, Agnes; Hanum, Luthfiah; Ilmi, Hanifah Mufidatul; Febriliani, Silvani (Universitas Negeri Surabaya, 2023)
The implementation of data security in academic systems is crucial to protect highlysensitive student, faculty, and administrative information. The ISO 27001 standard hasbecome a critical guide in the development and implementation of effective informationsecurity measures. This research aims to evaluate the use of ISO 27001 in the context ofUniversitas Negeri Surabaya (Unesa) and analyze its impact on data security in theacademic environment. The research identified risks relevant to Unesa's academic systems,including cyber threats and physical risks. The results of this study confirm that theimplementation of ISO 27001 has had a positive impact on data security at Unesa. Theimplementation of appropriate security controls and effective risk reduction has assisted inmaintaining the integrity of academic data and protecting valuable information assets. Assuch, Unesa students, lecturers and administrative staff feel more confident that their datais safe and secure. This research provides important insights into the key role played by theISO 27001 standard in securing academic systems in higher education institutions. It alsounderscores the importance of continuous risk evaluation, implementation of appropriatecontrols, and regular security monitoring as part of a successful data security strategy.